The 2025 Nobel Prize in Physics - Fabris, Júlio C. (Cadernos de Astronomia, 2025)
Brief comments by Brazilian physicists Ulysses Câmara da Silva (Federal University of Espírito Santo), Nelson Pinto Neto (Brazilian Center for Physics Research), and Olival Freire (Federal University of Bahia) on the 2025 Nobel Prize in Physics, which highlights work demonstrating quantum properties in non-microscopic systems.